IMPLEMENTASI PROGRAM KESEJAHTERAAN SOSIAL ANAK (PKSA) DALAM UPAYA PEMENUHAN KESEJAHTERAAN ANAK JALANAN (STUDI PADA SUKU DINAS SOSIAL JAKARTA TIMUR) - Ni Putu Ruslina Darmayanthi; Badrudin Kurniawan (Universitas Negeri Surabaya, 2022)
The Child Social Welfare Program (PKSA) is a form of directed, integrated, and sustainable effort by the government and the community in the form of social services and social welfare assistance for children. This program is guided by the Decree of the Minister of Social Affairs of the Republic of Indonesia Number 15 A/HUK/2010 concerning General Guidelines for Child Social Welfare Programs. One of the clusters of recipients of child services at PKSA is street children. Conditions on the reality show that there are still many street children whose social welfare has not been fulfilled and forces them to earn a living on the streets, especially in the East Jakarta area. This also shows that the implementation of PKSA is still not effective. Based on this, the purpose of this study is to describe the implementation of the Child Social Welfare Program at the East Jakarta Social Service Sub-dept. as an implementing agency, in an effort to fulfill the welfare of street children. The method used is a descriptive method with a qualitative approach. This study was analyzed using the theory of public policy implementation from Van Meter and Van Horn through six variables: policy standards and objectives; resource; communication between implementing agencies; the characteristics of the implementing agency; social, economic, and political environment; and attitude of the implementer. Based on the results of the research, the implementation of PKSA has been running according to the procedure, but there are still various obstacles, such as the lack of desire from street children to stop making money on the streets and the inability of the East Jakarta Social Sub-Department to accommodate the potential of street children. Suggestions that can be raised are, it is necessary to evaluate the strategy of the street children approach in order to minimize the coercive approach, expand cooperation with various parties to accommodate the potential of street children, and increase the number of human resources involved in this program. Keywords: Implementation, Social Welfare, Street Children